Issuance of Bank Back to Back Guarantee System Issuance at PT Bank Sulselbar Main Branch Makassar - Ruki Ambar Arum; Aris Baharuddin (Universitas Negeri Makassar, 2020)
This study aims understandof the System of Bank Guarantee issuance with Back –to-Back Form at PT Bank Sulselbar main Branch Makassar and the obstacle faced in the issuance of bank guarantee. The research used is descriptive qualitative which write describe the observation and the result of direct interview. The result showed that system of Bank Guarantee Issuance at PT bank Sulselbar main branch Makassar is Based on theory and government’ts regulation. But it needs additional officer at bank Guarantee section, so that the data entry is not late and the insuence of bank guarantee would be on time.